New algorithm for solving pentadiagonal CUPL-Toeplitz linear systems - Zhang, Yulin (2023)
In this paper, based on the structure of pentadiagonal CUPL-Toeplitz matrix and Sherman–Morrison–Woodbury formula, we develop a new algorithm for solving nonsingular pentadiagonal CUPL-Toeplitz linear system. Some numerical examples are given in order to illustrate the effectiveness of the proposed algorithms.